Method for efficiently preparing normal aldehyde from high-carbon olefin and application

By regulating the phosphine-containing polymer framework structure, an improved phosphine-containing polymer supported catalyst with a multi-stage pore structure was prepared, which solved the problem of low selectivity of orthoaldehyde in the hydroformylation reaction, and achieved a catalytic effect of high selectivity, high activity and low cost.

CN119569552APending Publication Date: 2025-03-07DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411692028.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the selectivity of orthoaldehydes in hydroformylation reactions, and the synthesis path of traditional phosphine ligands is complex, resulting in increased production costs and difficulty.

Method used

By replacing the template agent, regulating the phosphine-containing polymer framework structure, an improved phosphine-containing polymer supported catalyst with a multi-stage pore structure was prepared, and the active metal domain was used to limit the domain in the micropores to improve the selectivity of the aldehyde.

Benefits of technology

The selectivity of aldehydes is improved by 10%-50%, reducing production costs and improving production efficiency, while maintaining the high activity and long-range stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569552A_ABST
    Figure CN119569552A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the selectivity of normal aldehyde in a high-carbon olefin hydroformylation reaction, the catalyst takes one, two or more than two of metals Rh, Co, Ir, Ru, Pt, Pd and Fe as an active component, and a carrier is an improved phosphine-containing porous organic polymer. The heterogeneous catalyst provided by the invention has good performance in the hydroformylation reaction of high-carbon olefins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heterogeneous catalysis, and in particular relates to a method for preparing an improved phosphine-containing polymer supported catalyst and application of the catalyst in preparing normal aldehydes in a hydroformylation reaction. Background Art

[0002] Hydroformylation is one of the most important industrial reactions in the industry today. The reaction has been widely studied in the academic and industrial fields. The product aldehyde is a very important chemical intermediate. More than 12 million tons of aldehyde are produced by hydroformylation each year. Its derivatives have been used in the polymer and surfactant industries and the preparation of fine chemicals. When the carbon number of the olefin raw material is greater than 2, normal aldehydes and iso-aldehydes will be produced, among which the industrial products prepared from normal aldehydes have better performance. As a result, people began to study how to improve the selectivity of normal aldehydes. Phosphine ligands have been widely studied for their high activity. By rationally designing and modifying the electronic effect and stereostructure of phosphine ligands, the yield and selectivity of the target product can be effectively regulated. At present, with the heterogeneity of homogeneous catalysts, it is possible to have catalysts with high activity, high stability and high selectivity at the same time.

[0003] The selectivity of normal structural aldehydes can be improved by increasing the steric hindrance of the phosphine ligands, but the synthesis path of this method is complicated, the reaction process is numerous, and the production cost and difficulty are increased. Therefore, we consider regulating the microenvironment of the phosphine ligand, that is, replacing the template during the polymerization process, thereby changing the skeleton structure, increasing its micropores, and selecting the aldehyde at the micropores, thereby effectively improving the selectivity of normal structural aldehydes. Compared with traditional phosphine ligands, the improved phosphine ligands can further achieve the unity of high aldehyde selectivity and high normal structural aldehyde selectivity. Through a simple form, the purpose of improving the selectivity of normal structural aldehydes is achieved efficiently, reducing production costs and improving production efficiency. Summary of the invention

[0004] The purpose of the present invention is to adjust the skeleton structure of a phosphine-containing polymer by replacing a template agent, so as to prepare a self-supported catalyst with high normal structural aldehyde selectivity.

[0005] The technical solution of the present invention is:

[0006] A method for improving a phosphine-containing polymer supported catalyst for olefin hydroformylation reaction, characterized in that:

[0007] In the presence of an improved phosphine-containing polymer supported catalyst, a reaction liquid containing high carbon olefins is added, and synthesis gas is introduced to carry out a hydroformylation reaction;

[0008] The catalyst uses one, two or more of metals Rh, Co, Ir, Ru, Pt, Cu, Pd and Fe as active components, and the carrier is a phosphine-containing polymer improved by a template agent;

[0009] The catalyst carrier is polymerized from one or two phosphine ligands containing olefin groups; the phosphine ligands selected for the catalyst include one or more of all phosphine ligands, including but not limited to one or more of the following phosphine ligands, and the olefin group is preferably a vinyl group;

[0010]

[0011]

[0012]

[0013] Wherein: B1-B15 are multidentate phosphine ligands, P1-P17 are monophosphine ligands;

[0014] The template used in the improvement is alcohol, furan, ether, pyridine and aromatic solvents, preferably furan and aromatic solvents. The selected template is a mixture of one or two of the following solvents (including but not limited to):

[0015]

[0016]

[0017] The improved phosphine-containing polymer carrier has a multi-level pore structure and a specific surface area of ​​10-3000m 2 / g, preferably in the range of 100-1500m 2 / g, pore volume is 0.1-10.0cm 3 / g, preferably 0.2-2.0cm 3 / g, pore size distribution is 0.01-100.0nm, preferably 0.1-5.0nm;

[0018] The active component metal loading in the catalyst ranges from 0.01 to 10 wt %, preferably from 0.1 to 3 wt %. The preparation method of the improved phosphine-containing polymer supported catalyst is as follows:

[0019] The preparation process of the improved phosphine-containing polymer is as follows: under the protection of inert gas, a vinyl functionalized organic phosphine ligand monomer is dissolved in a template agent, and a free radical initiator is added, and the mixture is stirred at 273-473K (preferably 298-453K) for 0.2-4h (preferably 1h); then, the mixture is transferred to a hydrothermal synthesis kettle, and placed in an oven at 323-673K (preferably 373K) for 5-50h (preferably 24h); after cooling to room temperature, the mixture is taken out, a detergent is added to dissolve the mixture, and then the mixture is filtered at room temperature to replace the solvent required for polymerization, and then the mixture is filtered at 283-373K (preferably 293K-333K) to obtain an improved phosphine-containing polymer skeleton.

[0020] The preparation process of the improved phosphine-containing polymer supported catalyst is as follows: the precursor of the active metal component and the improved phosphine-containing polymer support are fully stirred and coordinated in a solvent, the active metal component forms a strong chemical bond with the exposed P in the improved phosphine-containing polymer support, and after evaporating the solvent, the improved phosphine-containing polymer supported catalyst is obtained.

[0021] The specific preparation method of the improved phosphine-containing polymer supported catalyst is:

[0022] a) mixing one or more of the templates under an inert gas atmosphere at 273-473K (preferably 298-453K), then adding a phosphine-containing ligand containing an olefin group, and then adding a free radical initiator, and stirring the mixture for 0.1-100 hours to obtain a prepolymer solution, preferably in the range of 0.1-20 hours;

[0023] b) transferring the prepolymer mixed solution obtained in step a) to a polymerization reactor, and performing polymerization reaction by one or more methods such as bulk polymerization, solution polymerization, suspension polymerization or emulsion polymerization for a polymerization time of 1-100 hours to obtain an improved phosphine-containing polymer;

[0024] c) adding a solvent to the improved phosphine-containing polymer obtained in step b) to dissolve it, filtering it at room temperature to displace the solvent required for polymerization, and filtering it at 283-373K (preferably 293-350K) to obtain an improved phosphine-containing polymer skeleton.

[0025] d) adding the improved phosphine-containing polymer support obtained in step c) to a solvent containing an active metal component precursor under an inert gas atmosphere at 283-373K (preferably 293K-333K), stirring for 0.1-100 hours, preferably 0.1-20 hours, and then removing the solvent at 273-403K (preferably 303-453K) to obtain an improved phosphine-containing polymer supported catalyst; the concentration of the active metal in the precursor solution is in the range of 0.001-1 mol L -1 .

[0026] The free radical initiator described in step a) is one or more of tert-butyl hydroperoxide, azobisisobutyronitrile, azobisisoheptanenitrile, cyclohexanone peroxide or dibenzoyl peroxide.

[0027] c) and d) are one or more of methanol, ethanol, dichloromethane, chloroform, benzene, toluene, xylene, water or tetrahydrofuran;

[0028] After the template is mixed in step a), the ratio of the several components is 0.01:1-100:1, preferably 1:1-1:30, the mass ratio of the template to the phosphine-containing ligand is 0.01:1-100:1, preferably 1:1-40:1, and the molar ratio of the phosphine ligand containing an olefin group to the free radical initiator is 500:1-10:1, preferably 100:1-10:1. Before polymerizing into an organic polymer, the concentration of the phosphine ligand containing an olefin group in the solvent ranges from 0.01-1000 g / L, preferably 0.5-50 g / L; the inert gas in steps a), b) and d) is selected from one or more of Ar, He, N2 and CO2.

[0029] The active component is one or more of Rh, Co, Ir, Ru, Pt, Pd or Fe, wherein the precursor of Rh is one or more of RhH(CO)(PPh3)3, Rh(CO)2(acac), RhCl3, and Rh(CH3COO)2; the precursor of Co is one or more of Co(CH3COO)2, Co(CO)2(acac), Co(acac)2, and CoCl2; the precursor of Ir is one or more of Ir(CO)3(acac), Ir(CH3COO)3, Ir(acac)3, and IrCl4; the precursor of Ru is dichloro(cyclooctyl-1,5-diene)ruthenium(II), RuCl3, Ru(acac)3, dodecacarbonyltriruthenium, [RuAr2(benze ne)]2, [RuAr2(p-cymene)]2, [RuAr2(mesitylene)]2, [(π-ally)Ru(cod)]2, [(π-ally)Ru(nbd)]2; the precursor of Pt is one or more of Pt(acac)2, PtCl4, PtCl2(NH3)2; the precursor of Pd is one or more of Pd(CH3COO)2, Pd(acac)2, PdCl2, Pd(PPh3)4, PdCl2(CH3CN)2; the precursor of Fe is one or more of Fe(acac)3, FeCl3, FeCl2, FeS, ferrocene, nonacarbonyl iron, and the metal loading in the catalyst is 0.01-10wt%, preferably 0.5-5wt%.

[0030] The improved phosphine-containing polymer supported catalyst is used in the olefin hydroformylation reaction, wherein the carbon number of the raw olefin is in the range of C3-C 30 .

[0031] Reaction principle of the present invention:

[0032] The present invention creatively adjusts the skeleton pore structure by changing the template agent during polymerization. The microporous structure in the adjusted skeleton is richer and the shape selectivity is stronger, thereby achieving the purpose of improving the selectivity of normal structural aldehydes. The catalyst protected by this patent is heterogeneous, the catalyst is easy to separate from the reaction system, and the catalyst is prepared by vinyl polymerization, the skeleton structure is stable, and the finally prepared catalyst has long-range stability and is suitable for industrial application.

[0033] The beneficial effects of the present invention are:

[0034] In the reaction process of high-carbon olefins, the selectivity of the product aldehyde of the triphenylphosphine polymer supported catalyst is very high, but the selectivity for the normal structural aldehyde is between 50% and 70%, and the content of the isomerized product is relatively high, making it difficult to achieve the maximum utilization of the product; the introduction of a bisphosphine ligand into the catalyst skeleton can significantly improve the selectivity for the normal structural aldehyde, but the preparation process of the functionalized bisphosphine ligand is very complicated. The present invention regulates the pore structure by regulating the microenvironment, so that the active metal is confined in the micropores, and the selectivity of the aldehyde is increased by 10%-50% in a low-cost manner, and the activity is not lost compared to the traditional catalyst, achieving high activity, high aldehyde selectivity, and high normal structural aldehyde selectivity. High efficiency and unity.

[0035] The supported catalyst prepared by the present invention is suitable for fixed bed, slurry bed, autoclave reactor and trickle bed reactors. The improved phosphine-containing polymer supported catalyst provided by the present invention shows good reaction performance in the hydroformylation reaction of high carbon olefins. The method for hydroformylation based on the improved phosphine-containing polymer supported catalyst involved in this patent is green and environmentally friendly, with less pollutant emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a scanning electron microscope image of Example 1;

[0037] Figure 2 is a transmission electron microscope image of Example 1;

[0038] Figure 3 is the physical adsorption diagram of Example 1;

[0039] Figure 4 This is the pore size distribution diagram of Example 1. DETAILED DESCRIPTION

[0040] The following examples are provided to better illustrate the present invention, but do not limit the scope of the present invention.

[0041] Example 1

[0042] The specific preparation process of the improved phosphine-containing polymer is as follows: under the protection of inert gas Ar at 300K, add 10.0g of the first component monomer P1 and 10.0g of the second component monomer P2, and dissolve them in 200ml of solvent E. Add 0.02g of free radical initiator azobisisobutyronitrile to the above solution, stir at room temperature for 4h to completely dissolve it, and obtain a prepolymer. Then transfer the prepolymer to a high-pressure reactor, and use bulk polymerization at 353K and the protective atmosphere of inert gas Ar for 30h. When the high-pressure reactor is cooled to room temperature, take out the obtained product, use 200ml of ethanol solution, centrifuge at 4000r / min in a high-speed centrifuge, then take out the solid, repeat the above process 3-5 times (here 4 times) to achieve solvent replacement, and then filter under a Buchner funnel. After the filtration is completed, remove the residual solvent at 333K to obtain the target product. From Figure 1 and Figure 2 Its pore distribution and adsorption state can be observed.

[0043] Preparation of improved phosphine-containing polymer self-supported catalyst: 8.0 mg of acetylacetonato carbonyl rhodium (CAS No. 14874-82-9) was weighed and dissolved in 20.0 ml of tetrahydrofuran solvent, 1.0 g of the above-prepared polymer was added, and stirred at 300K for 5 hours, and continued to stir for 5 hours at 300K under Ar gas protection, and the solvent was vacuum-evacuated at 330K to obtain a self-supported rhodium-based catalyst. The measured rhodium mass loading was 0.32%. Figure 3 and Figure 4 This indicates that the formed catalyst has a multi-level pore structure.

[0044] Example 2

[0045] In Example 2, except that 10.0 g of the second component P2 was not added, the rest of the synthesis process and conditions were the same as those of Example 1.

[0046] Example 3

[0047] In Example 3, except that 10.0 g of P8 was used to replace 10.0 g of the second component P2, the rest of the synthesis process and conditions were the same as those of Example 1.

[0048] Example 4

[0049] In Example 4, except that solvent G was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 1.

[0050] Example 5

[0051] In Example 5, except that solvent H was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 1.

[0052] Example 6

[0053] In Example 6, except that solvent I was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 1.

[0054] Example 7

[0055] In Example 7, except that solvent L was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 1.

[0056] Example 8

[0057] In Example 8, except that solvent P was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 1.

[0058] Example 9

[0059] In Example 9, except that solvent Q was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 1.

[0060] Example 10

[0061] In Example 10, except that the same molar number of acetylacetonato dicarbonyl iridium (I) was used to replace acetylacetonato carbonyl rhodium, the rest of the synthesis process and conditions were the same as in Example 1, and a highly dispersed Ir-based catalyst was obtained.

[0062] Embodiment 11

[0063] In Example 11, except that the same molar number of cobalt dichloride is used to replace acetylacetonato carbonyl rhodium, the rest of the synthesis process and conditions are the same as those in Example 1, and a highly dispersed Co-based catalyst can be obtained.

[0064] Example 12

[0065] In Example 12, except that the same molar number of ligand B1 was used instead of P1, the rest of the synthesis process and conditions were the same as those in Example 1.

[0066] Example 13

[0067] In Example 13, except that the same molar number of ligand B3 was used instead of P1, the rest of the synthesis process and conditions were the same as those in Example 1.

[0068] Embodiment 14

[0069] In Example 14, except that the same molar number of ligand B14 was used instead of P1, the rest of the synthesis process and conditions were the same as those in Example 1.

[0070] Embodiment 15

[0071] In Example 15, except that solvent G was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 2.

[0072] Example 16

[0073] In Example 16, except that solvent O was used instead of solvent E, the rest of the synthesis process and conditions were the same as those in Example 2.

[0074] Comparative Example 1

[0075] In Comparative Example 1, in addition to the solvent The solvent was replaced with D, and the other synthesis conditions were the same as those in Example 1.

[0076] Comparative Example 2

[0077] In Comparative Example 2, in addition to the solvent The solvent was replaced with D, and the other synthesis conditions were the same as those in Example 1.

[0078] Comparative Example 3

[0079] In Comparative Example 3, in addition to the solvent The solvent was replaced with D, and the other synthesis conditions were the same as those in Example 1.

[0080] Comparative Example 4

[0081] In Comparative Example 4, except that the solvent dichloromethane was replaced with solvent D, the other synthesis conditions were the same as those in Example 1.

[0082] Comparative Example 5

[0083] In Comparative Example 5, in addition to the solvent The solvent was replaced with D, and the other synthesis conditions were the same as those in Example 1.

[0084] 0.1 g of the catalyst prepared in Examples 1 to 16 and Comparative Examples 1-5, 1-hexene and 10 g of acetonitrile were added in an amount of S / C=8000, and the mixture was respectively loaded into a 50 ml reactor. A reaction mixture (H2:CO=1:1, V / V) was introduced, and the hydroformylation reaction was carried out for 5 h at 353 K, 1.0 MPa, and S / C=8000. The reaction product was centrifuged and separated into layers and allowed to stand. The obtained upper organic solution was analyzed by HP-7890N gas chromatography equipped with an HP-5 capillary column and an FID detector, using dioxane as an internal standard.

[0085] The reaction results are listed in Table 1.

[0086] Table 1 Specific surface area, pore size distribution and 1-hexene hydroformylation reaction data of the catalysts synthesized in Examples 1-16 and Comparative Examples 1-6

[0087]

[0088]

[0089] The metals used in Examples 10 and 11 are Ir and Co. It can be seen from the examples and comparative examples that different solvents have different specific surface areas and different selectivities for normal structural aldehydes, which is attributed to the adjustment of the solvents to their pore structures. It can be seen from Comparative Examples 1-6 that when some lipid solvents are selected, the specific surface area of ​​the synthesized polymer carrier is greatly reduced, further affecting its conversion rate and selectivity. When some solvents such as ethyl acetate and dichloromethane are selected, the normal-to-iso ratio is low and the output of normal structural aldehyde is less.

Claims

1. A method for catalyzing olefin hydroformylation using a phosphine-containing polymer supported catalyst, characterized in that: In the presence of a phosphine-containing polymer supported catalyst, a reaction liquid containing olefins is added, and then synthesis gas is introduced to carry out a hydroformylation reaction; The catalyst uses one, two or more of metals Rh, Co, Ir, Ru, Pt, Cu, Pd and Fe as active components, and the carrier is a phosphine-containing porous organic polymer improved by a template.

2. The method for improving a phosphine-containing polymer supported catalyst according to claim 1, characterized in that: The catalyst carrier is polymerized by one or two of the phosphine ligands containing olefin groups; the phosphine ligands used in the polymerization all contain olefin groups, wherein the olefin groups are preferably vinyl groups; the phosphine ligands include all phosphine ligands containing olefin groups including but not limited to one or more of the following phosphine ligands; The template used is a solvent such as alcohol, lipid, furan, ether, pyridine, aromatic, etc., preferably a mixture of one or two of furan and aromatic solvents. The template selected is preferably a mixture of one or two of the following solvents (including but not limited to):

3. The method according to claim 1 or 2, characterized in that: The phosphine-containing polymer carrier has a multi-level pore structure and a specific surface area of ​​10-3000m 2 / g, preferably in the range of 100-1500m 2 / g, pore volume is 0.1-10.0cm 3 / g, preferably 0.2-2.0cm 3 / g, pore size distribution is 0.01-100.0nm, preferably 0.1-5.0nm; The loading amount of the active component metal in the catalyst is in the range of 0.01-10 wt %, preferably in the range of 0.1-3 wt %.

4. A method according to any one of claims 1 to 3, characterized in that: The preparation process of the phosphine-containing polymer supported catalyst is as follows: 1) The preparation process of the improved phosphine-containing polymer is as follows: Under the protection of inert gas, the vinyl functionalized organic phosphine ligand monomer is dissolved in the template agent, and a free radical initiator is added, and the mixture is stirred at 0-60°C (preferably 20°C) for 0.2-4h (preferably 1h); then, the mixture is transferred to a hydrothermal synthesis reactor, and placed in an oven at 50-300°C (preferably 100-120°C) for 5-50h (preferably 24-36h); after cooling to room temperature, the mixture is taken out, a detergent is added to dissolve the mixture, and then the mixture is filtered at room temperature to replace the solvent required for polymerization, and then the mixture is filtered at 10-100°C (preferably 20°C-60°C) to obtain an improved phosphine-containing polymer skeleton; The preparation process of the improved phosphine-containing polymer supported catalyst is as follows: the precursor of the active metal component and the improved phosphine-containing polymer support are fully stirred and coordinated in a solvent, the active metal component forms a strong chemical bond with the exposed P in the improved phosphine-containing polymer support, and after removing the solvent, the improved phosphine-containing polymer supported catalyst is obtained.

5. The method according to claim 4, characterized in that: Specifically, a) adding a phosphine-containing ligand containing an olefin group to a mixture of one or more of the templates under an inert gas atmosphere at 273-473K (preferably 298-453K), and then adding a free radical initiator, and stirring the mixture for 0.1-100 hours to obtain a prepolymer solution, preferably in the range of 0.1-20 hours; b) transferring the prepolymer mixed solution obtained in step a) to a polymerization reactor, and performing polymerization reaction by one or more methods such as bulk polymerization, solution polymerization, suspension polymerization or emulsion polymerization for a polymerization time of 1-100 hours to obtain an improved phosphine-containing polymer; c) adding a solvent to the improved phosphine-containing polymer obtained in step b) to dissolve it, filtering it at room temperature to replace the solvent required for polymerization, and then filtering it at 10-100° C. (preferably 20° C.-60° C.) to obtain an improved phosphine-containing polymer skeleton; d) adding the improved phosphine-containing polymer support obtained in step c) to a solvent containing an active metal component precursor under an inert gas atmosphere at 273-473K (preferably 298-453K), stirring for 0.1-100 hours, preferably 0.1-20 hours, and then removing the solvent at 273-403K (preferably 303-453K) to obtain an improved phosphine-containing polymer supported catalyst; the concentration of the active metal in the precursor solution is in the range of 0.001-1 mol L -1 .

6. The method according to claim 5, characterized in that: The free radical initiator described in step a) is one or more of tert-butyl hydroperoxide, azobisisobutyronitrile, azobisisoheptanenitrile, cyclohexanone peroxide or dibenzoyl peroxide; The solvent in steps c) and d) is one or more of methanol, ethanol, dichloromethane, chloroform, benzene, toluene, xylene, water or tetrahydrofuran; The template used in the improvement is alcohol, furan, ether, pyridine and aromatic solvent, preferably furan and aromatic solvent.

7. The preparation method according to claim 6, characterized in that: After the template is mixed in step a), the ratio of the several components is 0.01:1-100:1, preferably 1:1-1:30, the mass ratio of the template to the phosphine-containing ligand is 0.01:1-100:1, preferably 1:1-40:1, and the molar ratio of the phosphine ligand containing an olefin group to the free radical initiator is 500:1-10:1, preferably 100:1-10:1; Before polymerization into an organic polymer, the concentration range of the phosphine ligand containing an olefin group in the solvent is 0.01-1000 g / L, preferably 0.2-20 g / L; the inert gas in steps a), b) and d) is selected from one or more of Ar, He, N2 and CO2.

8. The method according to claim 5, characterized in that: The active component is one or more of Rh, Co, Ir, Ru, Pt, Pd or Fe, wherein the precursor of Rh is one or more of RhH(CO)(PPh3)3, Rh(CO)2(acac), RhCl3, and Rh(CH3COO)2; the precursor of Co is one or more of Co(CH3COO)2, Co(CO)2(acac), Co(acac)2, and CoCl2; the precursor of Ir is one or more of Ir(CO)3(acac), Ir(CH3COO)3, Ir(acac)3, and IrCl4; the precursor of Ru is dichloro(cyclooctyl-1,5-diene)ruthenium(II), RuCl3, Ru(acac)3, dodecacarbonyltriruthenium, [RuAr2(benze ne)]2, [RuAr2(p-cymene)]2, [RuAr2(mesitylene)]2, [(π-ally)Ru(cod)]2, [(π-ally)Ru(nbd)]2; the precursor of Pt is one or more of Pt(acac)2, PtCl4, PtCl2(NH3)2; the precursor of Pd is one or more of Pd(CH3COO)2, Pd(acac)2, PdCl2, Pd(PPh3)4, PdCl2(CH3CN)2; the precursor of Fe is one or more of Fe(acac)3, FeCl3, FeCl2, FeS, ferrocene, nonacarbonyl iron, and the metal loading in the catalyst is 0.01-10wt%, preferably 0.5-5wt%.

9. The method according to claim 1, characterized in that: The carbon number range of the raw olefins is C3-C 30 .

10. The method according to claim 1, characterized in that: The reaction conditions of hydroformylation are as follows: the reaction process is to load the prepared catalyst into a 50ml reactor, add reaction raw materials and introduce synthesis gas, the reaction temperature is 333-573K (preferably 333-473K), and the reaction pressure is 0.5-12.0MPa (preferably 0.5-7.0MPa); the main components of the reaction raw material synthesis gas are H2 and CO, the volume content of (H2+CO) is 20-100% (preferably 50-100%), the volume ratio of H2 / CO is 0.5-5.0 (preferably 0.5-2.0), and the remaining gas components are one or more of CO2, N2, He, and Ar gas; the purity of the high-carbon olefin raw material is 20-100% (preferably 50-100%).